Suberanilohydroxamic acid (vorinostat) synergistically enhances the cytotoxicity of doxorubicin and cisplatin in osteosarcoma cell lines. Issue 10 (November 2016) - Pettke, Aleksandra; Hotfilder, Marc; Clemens, Dagmar; Klco-Brosius, Stephanie; Schaefer, Christiane; Potratz, Jenny; Dirksen, Uta
Abstract : Osteosarcoma is the most common primary bone cancer in children and is a highly malignant disease, in which 25% of patients present with metastasis at diagnosis. Considerable advances in the treatment of localized disease have been achieved since the introduction of combined modality treatment, increasing the prognosis of overall survival to 70%. Yet, established therapies have only limited success in treating both metastatic disease and nonresponders to primary chemotherapy. Therefore, new therapeutic approaches are required, particularly for the control of osteosarcoma in these patient groups. Epigenetically modifying substances are a class of emerging drugs that have shown therapeutic potential in various hematological and solid cancers. We examined the cytotoxic effects of 5-azacitidine, 3-deazaneplanocin A, and suberanilohydroxamic acid (SAHA) on osteosarcoma cell lines HOS, MG-63, MNNG, and ZK-58. SAHA was the only chemical agent that exerted a strong, growth-limiting effect in all cell lines tested. The growth-limiting effect of SAHA was accompanied by features characteristic of apoptotic death. We found that cotreatment with SAHA and cisplatin showed strong synergism in all cell lines. The effect of cotreatment with SAHA and doxorubicin was cell line dependent. In the cell lines HOS, MG-63, and MNNG, the combined effect was synergistic, whereas in the cell line ZK-58, SAHA antagonized doxorubicin. The strong synergism of SAHA indicated that in combination with cisplatin, it might enable a promising add-on to current therapy regimens. However, considering the cell line-dependent effect that was found when SAHA was combined with doxorubicin, further experimentation is needed.